ANALISIS KEMAMPUAN BERHITUNG SISWA KELAS III SEKOLAH DASAR MENGGUNAKAN MODEL TGT - Musa, Muhammad Maskur; Ismiyanti, Yulina; Sari, Yunita (STKIP Persada Khatulistiwa Sintang, 2025)
Learning should not be limited to the delivery of theoretical material, academic facts, or mere knowledge. Instead, it should be designed to provide opportunities for students to develop a wide range of essential competencies. This study aims to describe the implementation of the Teams Games Tournament (TGT) model as an innovative approach in mathematics learning to improve the arithmetic skills of third-grade students at SD Islam Sultan Agung 4. This research is a case study with a descriptive qualitative approach. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data presentation, and conclusion drawing techniques. Data validity was ensured through triangulation of sources, theories, researchers, techniques/methods, and time. The findings show that the implementation of the TGT model in mathematics learning involved three stages: planning, implementation, and evaluation. Through this model, students’ arithmetic abilities improved, as evidenced by increased performance in indicators such as understanding subtraction concepts, completing missing numbers, and applying various problem-solving strategies. Furthermore, students were able to solve word problems systematically and apply subtraction concepts in daily life.